Embryonic heritage: a unique case of Wolffian duct tumor in a 75-year-old female patient Modern approaches to morphological diagnostics - A. B. Villert; O. A. Bondyreva; S. V. Vtorushin; L. A. Kolomiets; M. O. Ochirov; A. A. Maltseva; S. A. Villert (Опухоли женской репродуктивной системы, 2025)
Female adnexal tumor of Wolffian origin is an extremely rare and poorly studied tumor arising from remnants of Wolffian (mesonephric) duct and having an ambiguous malignancy potential. Immunohistochemical diagnostics of these tumors is important to exclude other pathologies. Interpretation of the prognosis is ambiguous. There are no clear standards for surgical or chemotherapeutic treatment. This is due to the lack of a sufficient number of observations and clinical studies. The article presents a clinical case of Wolffian duct tumor diagnosed in a 75-year-old patient, with a discussion of the terminological, morphological, immunohistochemical and molecular genetic features of the tumor.